P-029 Mesenchymal stem cells inhibit saccular aneurysm pathogenesis in a rabbit model. (23rd July 2017) - Avery, M; Sen, A; Mitha, A
Abstract : Introduction: Intracranial aneurysms are relatively common entities, with rupture being a largely unpredictable event associated with significant morbidity and mortality. While current treatment modalities are effective at addressing mature aneurysms, disrupting aneurysm formation would potentially avoid the need for more invasive treatments. To inhibit saccular aneurysm pathogenesis would likely require blunting of the complex inflammatory cascade in the arterial wall. Mesenchymal stem cells (MSCs) are readily available cells found in adult tissues, such as bone marrow and adipose tissue, that have immunomodulatory properties and are immune evasive. 1 They have been studied as potential treatments for many diseases associated with inflammation and have shown promise for clinical translation. 2 While some studies have investigated MSCs as a treatment adjunct for aneurysms, none have examined their potential role in inhibiting aneurysm pathogenesis. We hypothesize that injecting MSCs IV will minimize the radiographic formation of aneurysms in a rabbit elastase-induced saccular aneurysm model by blunting the inflammatory process. Materials and methods: Thirteen New Zealand White Rabbits were randomly assigned to either control (n=5) or intervention (n=8) groups. All rabbits underwent right common carotid artery saccular aneurysm creation using approximately 35 units of elastase as previously described in this accepted and effective model. (3) At both the time of surgery and 14 days post-operatively, intervention group rabbits received an IV injection of 5 × 10 6 MSCs in 2 mL saline, while control group rabbits received 2 mL of vehicle. On day 28, the right femoral artery was cannulated in all rabbits and digital subtraction angiography performed. Aneurysm volume was calculated and compared between groups. Results: All rabbits tolerated the surgical procedures well with no peri-operative complications, and every procedure resulted in aneurysm formation. Mean volume of right common carotid saccular aneurysms in the control and intervention groups were 36.9 mm 3 and 15.4 mm 3, respectively. A Mann-Whitney U test was performed due to the heterogeneity of variances and found that the intervention group aneurysms were significantly smaller than control aneurysms (p=0.030). Conclusion: This is the first study investigating the ability of MSCs to inhibit the formation of saccular aneurysms. We postulate that the observed effects are secondary to MSC-induced inhibition of the initial inflammatory cascade of aneurysm pathogenesis. MSCs are known to have immunomodulatory effects in many other scenarios, either by migrating to a site of inflammation or by releasing factors from afar. 4 It is unclear by which mechanism the observed effect is occurring, but these findings suggest that MSCs may perhaps be utilized for inhibiting aneurysm formation. References: . Kean TH, Lin P, Caplan AI, Dennis JE. MSCs: Delivery routes and engraftment, cell-targeting strategies, and immune modulation. Stem Cells Int. 2013. 2013: Article ID732742. . Kim N, Cho SG. Clinical applications of mesenchymal stem cells. Korean J Intern Med2013;28:387–402. . Hoh BL, Rabinov JD, Pryor JC, Ogilvy CS. A modified technique for using elastase to create saccular aneurysms in animals that histologically and hemodynamically resemble aneurysms in human. Acta Neurochir 2004;146:705–711. . English K. Mechanisms of mesenchymal stromal cell immunomodulation. Immunol Cell Biol2013;91:19–26. Disclosures: M. Avery: None. A. Sen: None. A. Mitha: None.